Water Concessions : Who Wins, Who Loses, and What To Do About It - van den Berg, Caroline (World Bank, Washington, DC, 2012)
This note, based on the World Bank's Private Participation in Infrastructure (PPI) project database, reviews trends in infrastructure projects with private participation in low-income countries. Four main conclusions arise. Surprisingly, the proportion of countries with at least one project - eighty one percent - is higher among low-income, than middle-income countries. As in middle-income countries, most investment has been in telecommunications, or energy projects. However, in low-income countries, well over half the projects are greenfield. And the scale of private participation in low-income countries, lags far behind that in middle-income countries.